2004
DOI: 10.1007/s00595-004-2812-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Laparoscopic Rectopexy for Complete Rectal Prolapse in Patients Older than 70 Years Versus Younger Patients

Abstract: The outcome of laparoscopic rectopexy in elderly patients is similar to that in younger patients. Therefore, advanced age alone should not be a contraindication to laparoscopic rectopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…There was no difference in operation time between the laparoscopic and open rectopexy groups in our study. Our laparoscopic operating time was short compared to that of previous reports [3,5,[16][17][18]26]. However, the laparoscopic resection rectopexy took more time than the open operations.…”
Section: Surgical Outcomecontrasting
confidence: 64%
See 1 more Smart Citation
“…There was no difference in operation time between the laparoscopic and open rectopexy groups in our study. Our laparoscopic operating time was short compared to that of previous reports [3,5,[16][17][18]26]. However, the laparoscopic resection rectopexy took more time than the open operations.…”
Section: Surgical Outcomecontrasting
confidence: 64%
“…Perineal approaches have been reserved for elderly and unfit patients of high anesthetic risk. Kaiwa and co-workers [17] reported safe and effective results in nine elderly laparoscopically treated rectopexy patients who were in good general health (ASA I or II) and concluded that advanced age is not a contraindication to laparoscopic surgery, but a higher ASA score should be considered a contraindication. In our study, half of the patients were scored ASA III or IV (Table 1), but nevertheless the perioperative morbidity was minimal (Table 3).…”
Section: Surgical Outcomementioning
confidence: 97%
“…In addition, age alone is not a contradiction for this procedure, with good results and early recovery being seen even among the elderly [17][18][19].…”
Section: Discussionmentioning
confidence: 89%
“…Laparoscopic abdominal procedures have potential benefits of a minimally invasive approach, including less pain, shorter hospitalization, earlier recovery, and fewer complications, compared with open abdominal procedures. The study by Kaiwa et al [13] showed that there was no significant difference in the hospitalization, complications, or recurrences between nine patients older than aged 70 years and five patients younger (median age, 77 vs. 49 years). They concluded that advanced age alone should not be a contraindication to laparoscopic rectopexy.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, functional outcome and recurrence rates were similar between laparoscopic abdominal surgery and open surgery. Several studies have shown that laparoscopic surgery was as safe and feasible in elderly patients compared with younger patients [11][12][13]. Therefore, laparoscopic rectopexy with or without resection may a safe surgical option for elderly patients.…”
mentioning
confidence: 99%